Neonatal Urine Screening Program in the Province of Quebec: Technological Upgrade from Thin Layer Chromatography to Tandem Mass Spectrometry - Christiane Auray-Blais; Michel Boutin; Pamela Lavoie; Bruno Maranda (MDPI AG, 2021)
The Quebec Neonatal Urine Screening Program was initiated in 1971 with overall screening inception of newborns in 1973. Forty-seven years later, over 3.5 million babies have been screened for up to 25 inborn errors of metabolism divided into two groups: (1) urea cycle disorders and organic acidurias; and (2) disorders of amino acid metabolism and transport. The main goal of this preventive genetic medicine program is the detection of treatable diseases before the onset of clinical symptoms. Urine specimens from 21-day-old babies are collected and dried on filter paper by parents at home. The participation is voluntary with a high compliance rate over the years (~90%). Specimens are analyzed by thin layer chromatography (TLC). The main objective of this evaluative research project was to assess the feasibility of a technological upgrade towards mass spectrometry. A 2.85-min flow injection method was devised, normal values established, and abnormal profiles confirmed using second-tier tests. The validated assays are sensitive, specific, and suitable for populational screening, as well as for high-risk screening laboratories. Triple H syndrome, which would not be detected in newborns by blood screening at two days of age was found to be positive in the urine of an affected patient.